CROP: Cognitive radio ROuting Protocol for link quality channel diverse cognitive networks. (15th February 2018) - Singh, Jai Sukh Paul; Rai, Mritunjay Kumar
Abstract: Cognitive Radio is an emerging technology to overcome the problem of spectrum scarcity and underutilization. The vital requirement of Cognitive Radio Networks is quick route maintenance because of dynamic changing environment due to immediate emergence of Primary Users. The other major issue is the selection of path based upon shortest path or minimum hop while neglecting the Quality of the Links. The ultimate goal of routing metric is to choose a path that provides high throughput between the two end nodes, which is not possible as shortest path algorithm does not perform well in Multi-channel heterogeneous Cognitive Networks. Moreover, in multi-channel cognitive radio network the concatenated links between the nodes also deteriorates the overall network performance. In this paper C ognitive radio Ro uting P rotocol (CROP) is proposed for ad-hoc networks, which emphasis on these three major routing problems and provides solution for the same. The key novelty of this proposed routing protocol (CROP) are Smart Spectrum Selection (SSS) and Succeeding Hop Selection (SHS) methods. These methods allow the selection of available spectrum by the relay node in a single process and thereby make the route formation a simple process and even reduces the routing overhead. This not only quickens the spectrum sensing and selection but also enhances the throughput due to reduced overheads. Simulative analysis shows the performance of the proposed protocol in the various environmental conditions. Comparative analysis of the proposed metric is also performed, which shows that the Proposed CROP outperforms the available competing Cognitive Radio routing protocols.